Criminality and visual surveillance: an investigation into criminogenic space and vulnerable residential neighbourhood / Fazzami Othman - Othman, Fazzami (2022)
Natural surveillance and visibility are critical components of ensuring safety and development's long-term sustainability. By emphasising space utilisation and enhancing human movement, a safe space can be formed. Increased activity within a street space is thought to promote natural surveillance and contribute to sustaining the rate of visibility. However, whenever space activity is highlighted for crime prevention purposes, the result is invariably paradoxical. There is relatively few research examining the relationship between surveillance, visibility, and crime. Numerous studies that prioritise space utilisation indicate that permeable street design is more secure than impermeable street design. Furthermore, it is claimed that incorporating street space increased the risk of being a victim of insufficient defensive space. Meanwhile, a visibility study put a larger emphasis on housing design without taking environmental factors into consideration. Regardless of its method, the study lacks tangible evidence of how it might affect crime distribution. Thus, this research aims to determine which the local elements lead to a neighbourhood with insufficient surveillance and how visibility affects burglary distribution. Five neighbourhoods in Kuala Lumpur local council were chosen based on common characteristics, including fear of crime. To assess the amount of fear and the area's inter-visibility, this study used a quantitative research methodology that included sampling and the dwelling inventory approach. Additionally, a site verification was performed to ascertain the average daily traffic and local attributes. Numerous analyses were undertaken, including descriptive, visibility, spatial, and statistical. Through the use of a convex, axial map, and spatial accessibility inventory, the visibility study analysed both inter- and direct visibility. The spatial-temporal analysis used to determine the burglary pattern is intended to aid in visualising it. Additionally, the syntactic space method is used to gain a better understanding of how syntactic measures may affect visibility. Both analyses are then correlated and analysed statistically using correlation and regression analysis to detect and quantify significant correlations between independent and dependent variables. As the findings, locations with more visibility are safer and subject to greater public and private monitoring, but spaces with medium visibility can be both risky and safe. Spatial characteristics such as global integration, connectivity, and mean depth influence the rate of burglary. These spatial degrees allow natural public observation by passers-by, resulting in more safe space. As the output, a framework for a safer neighbourhood is designed, with a focus on visibility and surveillance. This framework was designed for the execution by critical law enforcement agencies, such as PlanMalaysia and local governments, which serve as policymakers and practitioners.